Identification of Flavonoid Content in Cucumis Sativus L. Peels with Dissimilar Polarity Solvents - Asman, Saliza; Mu’azzam Shah, Muhammad Azib; Zhe Yi, Lim; Fathihin Zarizan, Muhammad Amin (Journal of Science and Technology, 2024)
The study aimed to quantify flavonoid content in two types of Cucumis Sativus L. peels (regular and Japanese variants) using solvents with different polarities. The solvents utilized were water, 50% ethanol and 50% acetone which the yield was compared, and the flavonoid was extracted. The Shinoda test was employed to qualitatively determine the presence of flavonoids, indicated by changes to pale pink colour and colour disappearance upon the addition of HCl and magnesium ribbon. Quantitative analysis was performed using the aluminum chloride colorimetric method. Japanese cucumber peel extracted with 50% ethanol had the highest total flavonoid content (TFC) of 2.20 mg QE/g, while regular cucumber peel extracted with 50% ethanol had a total flavonoid content (TFC) of 1.20 mg QE/g. The study indicated that solvent polarity significantly influences flavonoid extraction, with ethanol being more effective for Japanese cucumber variants.